Environmental controls on the distribution of living (stained) benthic foraminifera on the continental slope in the Campos Basin area (SW Atlantic) - Yamashita, Cintia; Mello e Sousa, Silvia Helena de; Vicente, Thaisa Marques; Martins, Maria Virgínia; Nagai, Renata Hanae; Frontalini, Fabrizio; Godoi, Sueli Susana; Napolitano, Dante; Burone, Letícia; Carreira, Renato; Figueira, Rubens Cesar Lopes; Taniguchi, Nancy Kazumi; et al. (Journal of marine systems, 2018)
Living (stained) benthic foraminifera from deep-sea stations in the Campos Basin, southeastern Brazilian continental margin, were investigated to understand their distribution patterns and ecology, as well as the oceanographic processes that control foraminiferal distribution. Sediments were collected from 1050m to 1950m of water depth during the austral winter of 2003, below the Intermediate Western Boundary Current (IWBC) and the Deep Water Boundary Current (DWBC). Based on statistical analysis, vertical flux of particulate organic matter and the grain size of sediment seem to be the main factors controlling the spatial distribution of benthic foraminifera. The middle slope (1050m deep) is characterized by relatively high foraminiferal density and a predominance of phytodetritus-feeding foraminifera such as Epistominella exigua and Globocassidulina subglobosa. The occurrence of these species seems to reflect the Brazil Current System (BCS). The above-mentioned currents are associated with the relatively high vertical flux of particulate organic matter and the prevalence of sandy sediments, respectively. The lower slope (between 1350 and 1950m of water depth) is marked by low foraminiferal density and assemblages composed of Bolivina spp. and Brizalina spp., with low particulate organic matter flux values, muddy sediments, and more refractory organic matter. The distribution of this group seems to be related to episodic fluxes of food particles to the seafloor, which are influenced by the BCS at the surface and are deposited under low deep current activity (DWBC).